Does temporary transfer to preoperative hemodialysis influence postoperative outcomes in patients on peritoneal dialysis? A retrospective cohort study - Zhang, Yuyang; Zhou, Qingqing; Chen, Zeyang; Dong, Jie; Wang, Pengyuan (Frontiers in Surgery, 2023)
Background: The associations between preoperative transfer to hemodialysis (HD) and postoperative outcomes in patients on chronic peritoneal dialysis (PD) remain unknown. We conducted this retrospective cohort study to investigate whether preoperative HD could influence surgical outcomes in PD patients undergoing major surgeries. Methods: All chronic PD patients who underwent major surgeries from January 1, 2007, to December 31, 2020, at Peking University First Hospital were screened. Major surgery was defined as surgical procedures under general, lumbar or epidural anesthesia, with more than an overnight hospital stay. Patients under the age of 18, with a dialysis duration of less than 3 months, and those who underwent renal implantation surgeries and procedures exclusively aimed at placing or removing PD catheters were excluded. Patients involved were divided into either HD or PD group based on their preoperative dialysis status for further analysis. Results: Of 105 PD patients enrolled, 65 continued PD, and 40 switched to HD preoperatively. Patients with preoperative HD were significantly more likely to develop postoperative hyperkalemia. The total complication rates were numerically higher in patients undergoing preoperative HD. After adjustment, the incidence of postoperative hyperkalemia or any other postoperative complication rates were similar between groups. There were no differences in long-term survival between the two groups. Conclusions: It does not seem indispensable for PD patients to switch to temporary HD before major surgeries.